Prevalence of malocclusion in children with obstructive sleep apnoea. (6th September 2018) - Galeotti, Angela; Festa, Paola; Viarani, Valeria; D'Antò, Vincenzo; Sitzia, Emanuela; Piga, Simone; Pavone, Martino
Structured Abstract: Objectives: To describe the prevalence of malocclusions in 2‐ to 10‐year‐old children suffering from obstructive sleep apnoea (OSA) and to evaluate the association between occlusal variables and OSA. Setting and Sample Population: A total of 2101 consecutive patients referred to an otorhinolaryngology unit were considered for the study. One hundred and fifty‐six children (range 2‐10 years) with suspected OSA were selected for a sleep study. The final sample consisted of 139 children suffering from OSA and a control group of 137 children. Materials and Methods: All patients included in the study underwent a clinical orthodontic examination to record the following occlusal variables: primary canine relationship, presence of a posterior crossbite, overjet and overbite. Odds ratios and 95% confidence intervals, comparing the demographic characteristics and dental parameters in OSA vs non‐OSA children, were computed. Multivariable logistic regression models were developed to compare independent variables associated with OSA to non‐OSA children. Results: The prevalence of malocclusions in children with OSA was 89.9% compared to 60.6% in the control group ( P  < 0.001). Factors independently associated with OSA compared to the control group were posterior crossbite (OR = 3.38; 95%CI:1.73‐6.58), reduced overbite (OR = 2.43; 95%CI:1.15‐5.15.), increased overbite (OR = 2.19; 95%CI:1.12‐4.28) and increased overjet (OR = 4.25; 95%CI:1.90‐9.48). Conclusions: This study showed a high prevalence of malocclusion in children with OSA compared to the control group. The posterior crossbite and deviations in overjet and overbite were significantly associated with OSA. The presence of these occlusal features shows the importance of an orthodontic evaluation in screening for paediatric OSA.